2021
DOI: 10.1002/ijgo.13714
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of the prevalence of endocrine disorders in pregnancies complicated by coronavirus disease 2019: A narrative review with meta‐analysis

Abstract: Background Some maternal characteristics indicate worse prognosis in pregnant women with coronavirus disease 2019 (COVID‐19). Objective To describe the prevalence of endocrine disorders in pregnancies involving COVID‐19, and its impact on maternal outcomes. Search strategy Search terms were “pregnancy” and “COVID‐19”. Selection PubMed, Embase, medRxiv, and Cochrane worksheet from February to July 2020 were searched. Data collection and analysis Articles describing endocrine disorders in pregnancies with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This is a secondary analysis of data collected for a systematic review [ 7 ]. The review project was approved on 18 August 2020 by the Research Ethics Committee of the Hospital de Clínicas de Porto Alegre, Brazil (CAAE 35017020600005327), under number 2020-0382.…”
Section: Methodsmentioning
confidence: 99%
“…This is a secondary analysis of data collected for a systematic review [ 7 ]. The review project was approved on 18 August 2020 by the Research Ethics Committee of the Hospital de Clínicas de Porto Alegre, Brazil (CAAE 35017020600005327), under number 2020-0382.…”
Section: Methodsmentioning
confidence: 99%
“…Reichelt et al [30] reported that the prevalence of obesity and hyperglycemia were increased in pregnancies complicated with severe SARS-CoV-2 infection. The pandemic confinement also increased the risk of hypothyroxinemia during the first and second trimesters of pregnancy [31].…”
Section: Pre-gestational Co-morbiditymentioning
confidence: 99%